An analysis of gasparin's didactics: the possibility of pedagogical praxis? (Research, Society and Development, 2019)
The aim of the article is to analyze the didactic proposal of Gasparin (2013) from the work titled "A didactic for historical-critical pedagogy", embodied in the methodology proposed by Professor Dermeval Saviani, which addresses this pedagogy as being An alternative to overcoming the liberal approaches of teacher training in recent decades. The work brings the explanation of the five steps of the pedagogical method proposed by Saviani (2011), synthesized in the didactics of João Luiz Gasparin. As a central question: how to work the pedagogical praxis that promotes the integral education of the students based on the contributions of the didactics of Gasparin grounded in the principles of historical-critical pedagogy (PHC)? The methodology is part of the bibliographic research pertinent to the proposed theme and its epistemological foundations in Marx's historical-dialectical materialism, with a qualitative approach. It seeks as a goal to obtain theoretical knowledge to reach the teaching practice in a historical-critical perspective based on didactic contributions that evidence the feasibility of social transformation of professors and students. The results show that there is a possibility of applying the method that attempts to work the teaching proposal based on the historical-critical pedagogy, thus breaking with the models of liberal approaches and it was also found that through the Socialization of systate knowledge is possible to succeed in integral human formation and social transformation of students. We conclude that in the Gasparin method the teaching work is more dynamic and the dialectical process of practice-theory-practice leads the student to perceive that the contents to be studied establish a relationship with reality and with the totality of social and historical practice.